Modelos de puntos de inflexión para evaluar la evolución de la carga de cáncer de pulmón en Perú, 1990–2021 - Prudencio León, Walter Enrique (2026)
Objective: To analyze the temporal trends and sex differences in lung cancer burden in Peru between 1990 and 2021, and to evaluate the impact of trend changes on public health. Materialsand methods: A time-series study was conducted using the age-standardized rates of incidence, prevalence, mortality, and disability-adjusted life years (DALYs) extracted from the Global Burden of Disease (GBD) Study 2021. Trends were assessed using the joinpoint regression model, and the average annual percent change (AAPC) was calculated for the entire period, along with segmentedannual percent changes (APCs). The overall results were contrasted with the sex-disaggregated analysis. Results: The overall trend showed a significant reduction in DALYs and years of life lost (YLLs) (AAPC = −1.01%) and mortality (AAPC = −0.87%), largely driven by the decline in male mortality (AAPC = −1.57%). However, this overall improvement was overshadowed by sex-specific divergences (stagnation in female incidence [AAPC ≈ 0%]) and the acute crisis observed during 2015–2019. Segmented analyses revealed a parallel and significant increase across all fourmetrics during this period: Incidence (APC: males +3.59%, females +5.64%), prevalence (APC up to +6.57%), and DALYs/YLLs (APC up to +5.79%). This increase in overall burden and mortality demonstrates that the rise in new cases nullified survival gains achieved through policies such as Peru’s Plan Esperanza (national plan for comprehensive cancer care), resulting in a public health setback. Conclusions: The reduction in lung cancer burden in Peru is fragile. The incidence and mortality crisis of 2015–2019 demonstrates that improvements in therapy are being outpaced by failure in primary prevention, especially in the female population. Urgent reallocation of resources toward primary prevention, including attention to non-tobacco risk factors, is essential to sustain reductions in disease burden in the coming decades.